Herkunft, Aufbau und Bewertung der Flugsande im Binnenlande - Schelling, Jacobus (ERDKUNDE, 1957)
The formation of sand dunes along the coast and inland show typical differences. Inland the source of sand supply is the sandy area itself. There we find also pronounced soil profiles and thus a greater resistance against erosion. Although the vegetation on inland dunes suffers less through wind and salinity, against this should be set the fact that blown sand is poorer in plant food, is of lesser lime content and contains fewer heavy minerals. The organic matter which occurs in profiles of blown sand in the form of narrow bands was mainly formed in situ. There is a striking connexion between the occurrence of sheet sand and blown sand. Fluvioglacial as well as preglacial sands which were pushed up by the ice are rarely shifted by the wind; they do, however, frequently come to the surface as a result of wind action. Generally speaking it could be said that blown sand originates from dry and high lying sheet sand in places where the vegetation has been destroyed by man. Surface depressions act as sand catchers and in the long run cause an inversion of the relief. In areas where remains of the wind eroded surface prevail, the following forms are found: the fort, a plateau dune of blown sand with steep slopes, and further table shaped dunes and blown out depressions. Strictly speaking the latter cannot be called dunes, they are the flat or nearly flat gently undulating parts of the areas of blown sand; in most cases they lack a soil profile and the C horizon is at surface level. In those cases where remains of the wind eroded surface are of little or no importance the following formations are found; dunus lingulatus, dunus verticosus and dunus prismaticus. These are passive obstacle dunes (duni obsidionates passivi). On bare surfaces passive migratory dunes (duni migratores passivi) occur. Moving barchans (duni falcati) and longitudinal dunes (duni falcates lineari) are almost absent in the Veluwe area. Drifted into dense vegetation, forest or shrubs, are the offensive obstacle dunes (duni obsidionales aggressivi). They are often found at the transition from dry to humid areas. Aggressive migratory dunes (duni migratores aggressivi) occur also. Advanced erosion often makes morphological identification impossible. The value of areas of blown sand for recreation purposes is mainly due to an appreciation of their vegetation and the drifting movement of the white sand. The hilly character as well as the difficulties encountered in crossing areas of blown sand make this type of landscape attractive for military training. As a result other areas of greater land use value can be spared. The blown sand soils are unsuitable for either arable cultivation or market gardening, except for growing of asparagus. The possibility of deep rooting enables forest to flourish reasonably well on those blown sand soils with a moderate humus content.